2022
DOI: 10.1007/s10719-021-10039-3
|View full text |Cite
|
Sign up to set email alerts
|

Methyl β-D-galactopyranoside esters as potential inhibitors for SARS-CoV-2 protease enzyme: synthesis, antimicrobial, PASS, molecular docking, molecular dynamics simulations and quantum computations

Abstract: Carbohydrate esters are significant in medicinal chemistry because of their efficacy for the synthesis of biologically active drugs. In the present study, methyl β-D-galactopyranoside (MGP) was treated with various acyl halides to produce 6- O -acyl MGP esters by direct acylation method with an excellent yield. To obtain newer products for antimicrobial assessment studies, the 6- O -MGP esters were further modified into 2,3,4-tri- O -acyl MGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 58 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…A sixteen-proton multiplet at δ 1.29 {CH 3 (CH 2 ) 8 (CH 2 ) 2 CO-} and three-proton multiplet at δ 0.90 {CH 3 (CH 2 ) 10 CO-} were also seen. These ndings rationalized the appearance of a lauroyl group in the position 2 as depicted by the deshielding of the C-2 proton from its common value (~ 4.00) [29] in the initial diol (2) to δ 4.83 (as dd, J = 3.7 Hz, and 9.7 Hz). The 13 13 C-NMR and mass spectrum led us to con rm the structure of compound (3) as methyl 4,6-O-benzylidine-2-O-lauroyl-α-D-glucopyranoside (Table 1).…”
Section: Reagents and Conditionsmentioning
confidence: 60%
“…A sixteen-proton multiplet at δ 1.29 {CH 3 (CH 2 ) 8 (CH 2 ) 2 CO-} and three-proton multiplet at δ 0.90 {CH 3 (CH 2 ) 10 CO-} were also seen. These ndings rationalized the appearance of a lauroyl group in the position 2 as depicted by the deshielding of the C-2 proton from its common value (~ 4.00) [29] in the initial diol (2) to δ 4.83 (as dd, J = 3.7 Hz, and 9.7 Hz). The 13 13 C-NMR and mass spectrum led us to con rm the structure of compound (3) as methyl 4,6-O-benzylidine-2-O-lauroyl-α-D-glucopyranoside (Table 1).…”
Section: Reagents and Conditionsmentioning
confidence: 60%
“…The growth of the strains on MDM (MLR, MLS, and MLSLR) also revealed the upregulation in the expression of methyl-galactoside, a beta-Dgalactopyranoside (a monosaccharide derivative) with a methyl substituent at the anomeric position. Methylgalactoside was recently reported to possess potential antimicrobial activities against Bacillus subtilis, Escherichia coli, and in-silico ability to inhibit SAR-CoV-2 by binding proteases 39 . Another study by Amin et al 40 revealed that acylation of beta-D-galactopyranoside with different acyl halides resulted in methyl esters with antifungal, antibacterial and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…The potential probiotic strains in this study can produce beta-D-galactopyranoside, especially in MDM, which supports their potential for use in precision probiotic therapy if properly harnessed. Additionally, methyl-galactoside was involved in cell-to-cell binding and co-aggregation 39 .…”
Section: Discussionmentioning
confidence: 99%
“…They are the source of the metabolic energy supply and are also useful for the fine-tuning of cell-cell interactions and other crucial processes (Varki 1993;Seeberger and Werz 2007). It was found from the literature survey that a large number of biologically active compounds also possess aromatic, heteroaromatic, and acyl substituents (Amin et al 2021(Amin et al , 2022Lepenies et al 2010;Rana et al 2020;Bulbul et al 2021a, b;Arifuzzaman et al 2018;Maowa et al 2021a;Alam et al 2021a). The benzene, substituted benzene, and also nitrogen, sulfur, and halogen-containing substituents are known to enhance the biological activity of the parent compound (Rana et al 2021;Farhana et al 2021a;Devi et al 2019;Alam et al 2021b).…”
Section: Introductionmentioning
confidence: 99%